2020
DOI: 10.1101/2020.08.31.274639
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Drug repurposing screen identifies masitinib as a 3CLpro inhibitor that blocks replication of SARS-CoV-2in vitro

Abstract: There is an urgent need for anti-viral agents that treat SARS-CoV-2 infection. The shortest path to clinical use is repurposing of drugs that have an established safety profile in humans. Here, we first screened a library of 1,900 clinically safe drugs for inhibiting replication of OC43, a human beta-coronavirus that causes the common-cold and is a relative of SARS-CoV-2, and identified 108 effective drugs. We further evaluated the top 26 hits and determined their ability to inhibit SARS-CoV-2, as well as othe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
48
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 44 publications
5
48
0
Order By: Relevance
“…In the case of Bafetinib, a Lyn/Bcr-Abl inhibitor which has off-target activity against SRC the IC 50 was in the nanomolar range ( IC 50 : 0.79 µM, 95% confidence interval 0.23-1.35 µM). Bafetinib has recently been independently identified as an inhibitor of the coronaviruses OC43 and SARS-COV-2 in a large-scale drug-repurposing screen (35). Inhibition with Sorafenib which was included as a positive control and does not directly target any of the protease substrates was in the low micromolar range (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of Bafetinib, a Lyn/Bcr-Abl inhibitor which has off-target activity against SRC the IC 50 was in the nanomolar range ( IC 50 : 0.79 µM, 95% confidence interval 0.23-1.35 µM). Bafetinib has recently been independently identified as an inhibitor of the coronaviruses OC43 and SARS-COV-2 in a large-scale drug-repurposing screen (35). Inhibition with Sorafenib which was included as a positive control and does not directly target any of the protease substrates was in the low micromolar range (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…research. Drug screening studies showed that many drugs that inhibit replication of OC43 also inhibit SARS-CoV-2 in vitro 17 . First, we infected human lung epithelial A549 cells with coronavirus OC43 at a multiplicity of infection (MOI) of 1 and fixed the cells with PFA, along with a fixed mock infected sample, and performed FD-seq.…”
Section: Fd-seq Reveals Pro-inflammatory Bystander Cells After Coronamentioning
confidence: 99%
“…OC43, like SARS-CoV-2, belongs to the family of betacoronaviruses, and is a major human pathogen that causes the common cold. OC43 has been successfully used to discover drugs that inhibit SARS-CoV-2 replication in vitro 17 . We found that human lung cells infected by OC43 were composed of two subpopulations with either low or high viral gene expression.…”
Section: Introductionmentioning
confidence: 99%
“…We have already begun to share the biosensor and other related reagents with laboratories around the world. Indeed, the biosensor assay was recently used to verify that an antiviral drug that inhibits replication of SARS-CoV-2 targets 3CLpro ( Drayman et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%